Canada. Significant achievements 2010-2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Canada are identified, during the period from 2010 to 2017, with respect to the needs and interests of the country, strengthening issues such as exports, beekeeping, loss reduction, use of greenhouses, research , agroforestry management, plant and animal health, food safety. Likewise, work was done to improve livestock, through genetic studies combating diseases in animals, in the value chains of ruminants, fruits and potato seeds. Finally, support was given to the inclusion of young people in agricultural issues and small and medium-sized entrepreneurs.